Advances in Traditional Chinese Medicine for the Treatment of Diabetic Nephropathy from the Perspective of Glycolipid Metabolism - Liu, Hongfeng; Huyan, Xiaoting; Zhang, Ziqing; Zhao, Yafeng; Zhang, Nan; Li, Xiancheng; Qu, Kai (Journal of Contemporary Medical Practice, 2025)
Diabetic kidney disease (DKD) is a major and severe chronic complication of diabetes, with a multifactorial pathogenesis involving glycolipid metabolism disorders, inflammation, oxidative stress, and glomerular injury. Emerging evidence highlights glycolipid metabolism disorders as a central driver in the development and progression of DKD. In traditional Chinese medicine (TCM), DKD is classified under “Xiaoke-related kidney disease,” “edema,” and “deficiency-fatigue syndromes,” with its pathogenesis characterized by deficiency in the spleen and kidney and excess due to phlegm-turbidity, blood stasis, and damp-heat. The concept of “internal obstruction by phlegm-turbidity” aligns with the pathological role of glycolipid disorders. Modern pharmacological and clinical studies further demonstrate that TCM interventions can regulate glycolipid metabolism, improve insulin resistance, and suppress inflammatory and oxidative stress pathways, thereby delaying renal damage. This review discusses the pathogenesis and progression of DKD from the perspective of glycolipid metabolism, providing a theoretical basis for the application of TCM in its treatment.